Assessment of oxidative stress in serum of pulmonary tuberculosis patients - Wagh, Vishal; Rajopadhye, Shreewardhan; Mukherjee, Sandeepan; Urhekar, Anant; Modi, Deepak (International Journal of Research in Medical Sciences, 2017)
Background: Tuberculosis (TB) remains a human health issue and often deadly infectious disease in low-middle income nations. In TB, oxidative stress is a result of tissue inflammation, poor dietary intake of micronutrients due to illness, free radical burst from activated macrophages. This study was conducted prospectively to evaluate the oxidative stress in TB. Methods: The study included 30 newly diagnosed TB positive patients and 30 healthy individuals. Pro-oxidant markers like the thiobarbituric acid reactive species (TBARS) and nitric oxide were studied from serum. Antioxidant parameter like serum total-SH was also assessed. Results: Levels of pro-oxidants were significantly increased whereas antioxidant defense markers were significantly impaired in the TB group. Nitric oxide and TBARS were increased (p<0.0001) where glutathione was decreased (p<0.0001) in TB population compared to healthy controls. Conclusions: Marked oxidative stress were seen in the TB population as compared to the healthy cohort. The role of antioxidant therapy may therefore be evaluated in the management of TB.